Sharing Online Health Information With Physicians: Understanding the Associations Among Patient Characteristics, Directness of Sharing, and Physician-Patient Relationship - Li, Siyue; Wang, Kexin (Frontiers in Psychology, 2022)
Patients increasingly seek and share online health information with their physicians. However, few studies have investigated factors that may facilitate or inhibit such sharing and subsequent impact on physician-patient relationship. This study conducted a cross-sectional survey among 818 Chinese patients to examine if two patient characteristics -communication apprehension and eHealth literacy- influence their ways of sharing online health information with physicians and subsequently impact physician-patient relationship. The results showed that a majority of surveyed participants searched health information online, and about half of them used such information during their doctor visits. Less apprehensive patients tend to share the information with their physicians more directly, which can positively affect perceived physician reactions and patient satisfaction. eHealth literacy, however, is not found to be associated with patients’ sharing of online information with physicians. This study underscores the importance of identifying patient characteristic’s role in patient-physician interaction.